2017
DOI: 10.1094/mpmi-11-16-0233-r
|View full text |Cite
|
Sign up to set email alerts
|

WHOP, a Genomic Region Associated With Woody Hosts in thePseudomonas syringaeComplex Contributes to the Virulence and Fitness ofPseudomonas savastanoipv.savastanoiin Olive Plants

Abstract: Bacteria from the Pseudomonas syringae complex belonging to phylogroups 1 and 3 (PG1 and PG3, respectively) isolated from woody hosts share a genomic region herein referred to as WHOP (from woody host and Pseudomonas spp.), which is absent in strains infecting herbaceous organs. In this work, we show that this region is also encoded in P. syringae pv. actinidifoliorum (PG1) and six additional members of PG3, namely, Pseudomonas savastanoi pv. retacarpa, three P. syringae pathovars, Pseudomonas meliae, and Pseu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 79 publications
1
33
0
Order By: Relevance
“…A cluster of genes named WHOP (woody hosts and Pseudomonas) thought to be involved in aromatic compound (lignin) degradation (Caballo-Ponce et al, 2016) was present in Psm R1 and R2, whilst P. syringae pv avii and most Pss strains contained no WHOP homologues. Two cherry P2d strains (syr2339 and syr7924) did, however, possess the catechol catBCA cluster.…”
Section: Search For Virulence Factorsmentioning
confidence: 99%
“…A cluster of genes named WHOP (woody hosts and Pseudomonas) thought to be involved in aromatic compound (lignin) degradation (Caballo-Ponce et al, 2016) was present in Psm R1 and R2, whilst P. syringae pv avii and most Pss strains contained no WHOP homologues. Two cherry P2d strains (syr2339 and syr7924) did, however, possess the catechol catBCA cluster.…”
Section: Search For Virulence Factorsmentioning
confidence: 99%
“…A cluster of genes named WHOP ( w oody h osts and P seudomonas ) thought to be involved in aromatic compound (lignin) degradation (Caballo-Ponce et al ., 2016) was present in Psm R1 and R2, whilst P.s pv. avii and most Pss strains contained no WHOP homologues.…”
Section: Search For Virulence Factorsmentioning
confidence: 99%
“…aesculi isolated from horse chestnut (Green et al, 2010), and found to be absent in the genomes of P. syringae strains infecting herbaceous hosts. Subsequent genomic analyses determined that the presence of this cluster, currently referred to as the WHOP region (from w oody ho st and P seudomonas ) (Caballo-Ponce et al, 2017), is a feature exclusive to strains of phylogroups (PGs) 1 and 3 of the P. syringae complex isolated from woody organs of woody hosts, suggesting a specific role of this region in bacterial adaptation to woody tissues (Ramos et al, 2012; Bartoli et al, 2015; Nowell et al, 2016; Caballo-Ponce et al, 2017). In agreement with this hypothesis, the ability of several strains of the P. syringae complex, including Psv strains NCPPB 3335 and PseNe107, to grow endophytically in kiwi trees has been associated with codification of the cat operon (Bartoli et al, 2015).…”
Section: A Whop Makes the Difference: Metabolism Of Phenolic Compoundmentioning
confidence: 99%
“…Genes in this region are organized into four different operons ( catBCA , antABC , ipoABC , and dhoAB ) and three independently transcribed genes ( antR , benR and a gene encoding a putative aerotaxis receptor). Although no function has yet been attributed to the dhoAB operon, the involvement of the Psv NCPPB 3335 antABC and catBCA operons in the catabolism of anthranilic acid and catechol, respectively, has been confirmed; additionally, the ipoABC operon was associated to an oxygenase activity acting on aromatic compounds (Caballo-Ponce et al, 2017). Nonetheless, the most intriguing conclusions of this work are derived from the role of the WHOP region during bacterial interactions with olive plants.…”
Section: A Whop Makes the Difference: Metabolism Of Phenolic Compoundmentioning
confidence: 99%
See 1 more Smart Citation